2007
DOI: 10.1007/s00432-007-0243-8
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell-derived IL-1α induces IL-8 release in endothelial cells

Abstract: IL-1alpha is constitutively expressed in many human cancer cells and directly induces IL-8 secretion in neighboring endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Targeting of IL‐1α or IL‐8 effectively inhibited phosphorylation of STAT3, decreased EMT and suppressed the invasiveness of breast cancer cells. In previous studies, IL‐1α and IL‐8 were found to be highly expressed in breast cancer compared with normal breast tissue, and associated with poor prognosis . Pantschenko et al .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Targeting of IL‐1α or IL‐8 effectively inhibited phosphorylation of STAT3, decreased EMT and suppressed the invasiveness of breast cancer cells. In previous studies, IL‐1α and IL‐8 were found to be highly expressed in breast cancer compared with normal breast tissue, and associated with poor prognosis . Pantschenko et al .…”
Section: Discussionmentioning
confidence: 92%
“…In previous studies, IL-1a and IL-8 were found to be highly expressed in breast cancer compared with normal breast tissue, and associated with poor prognosis. (23)(24)(25)(26) Pantschenko et al (23) suggest that the IL-1 family of cytokines are present within human breast cancer and trigger other protumorigenic cytokines in tumor microenvironment, such as the angiogenic factor and growth factor including IL-8. In addition, they demonstrate that expression levels of some members of the IL-1 ⁄ IL-8 network of cytokines are correlated with prognostic indicators such as estrogen and progesterone receptors.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, we wondered whether Gzm B-mediated processing of IL-1α could impact upon its biological activity. To explore this issue, we measured the ability of IL-1α to stimulate production of IL-6 and IL-8 from HeLa cells and primary HUVECs, as both cell types are known to respond to this cytokine (Bertelsen and Sanfridson, 2007; Rhim et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Using a HUVEC in vitro model, cancer cells were shown to secret interleukin (IL)-1α to stimulate IL-8 secretion by endothelial cells [41]. Moreover, conditioned medium of the A549 lung cancer cell line regulates endothelial cell platelet derived growth factor (PDGF) expression which is VEGF dependent [42].…”
Section: Discussionmentioning
confidence: 99%